Faktor Determinan Kejadian Stunting dan Overweight-Obesitas Pada Siswi Remaja Putri: Determinants of Co-Occurrence Stunting and Overweight-Obesity in School-Aged Adolescent Females - Patimah, Sitti; Yasin, Yade Kurnia; Sharief, Suchi Avnalurini; Rachmat, Muhammad (Universitas Airlangga, 2026)
Background: The nutritional transition has led to a shift from a single nutritional problem to a double burden of malnutrition, particularly in adolescent females. Objectives: This study aims to explore the determinants of the co-occurrence of stunting and overweight-obesity in adolescent females. Methods: A cross-sectional method was applied to all female adolescents of school age (n = 360) from 4 secondary schools in Majene, West Sulawesi, Indonesia, between March and April 2021. Data were obtained through the use of a structured questionnaire, 24-hour dietary recall, and measurements of body weight and height. Analysis of the data was conducted using SPSS, NutriSurvey, and WHO AnthroPlus, with statistical significance at the 5% level (95% confidence interval). Results: The results showed that among participants aged 10–19 years, 31.7% were stunted, 14.2% were overweight, 2.2% were obese, and 2.5% experienced both stunting and overweight-obesity. Intake of protein, fat, and magnesium was significantly related to stunting and overweight-obesity (p-value = 0.004, 0.049, and 0.016, respectively). According to the multilevel regression analysis, nutritional knowledge (AOR=6.880; 95% CI: 1.189–39.804; p-value=0.031) and fiber intake (AOR=25.830; 95% CI: 1.565–426.370; p-value=0.023) were significant contributors to the co-occurence. Conclusions: Nutritional knowledge and dietary intake are significant predictors of stunting and overweight-obesity in adolescent females. Therefore, the enhancement of school-based nutritional literacy programs and the creation of a supportive school environment that promotes nutritional status are recommended.